The impact of strategic thinking on organizational excellence: An empirical examination in Jordan’s ICT sector - Lina Al-Abbadi; Mohammad A.K Alsmairat; Rawan Alshawabkeh; Amani Abu Rumman (International Journal of Data and Network Science, 2024)
This study empirically examines the impact of strategic thinking on organizational excellence in Jordan's Information and Communication Technology (ICT) sector. Adopting a quantitative methodology, this study surveys a sample of 270 individuals drawn from various ICT companies across Jordan. Utilizing Structural Equation Modeling (SEM) with Partial Least Squares (PLS) for analysis, the study investigates the effects of different dimensions of strategic thinking on organizational excellence. The findings reveal that among the dimensions studied, dynamic and systematic thinking significantly and positively influenced organizational excellence. These results underscore the critical role that adaptive and methodical approaches to strategic thought play in enhancing organizational performance and competitiveness within the fast-paced ICT sector. The study not only contributes to the theoretical understanding of strategic thinking's relevance in organizational success but also offers practical insights for ICT companies aiming to achieve excellence in a dynamic business environment.